PENGARUH PEER GROUP SUPPORT TERHADAP SELF CARE KLIEN HIPERTENSI - Nihayatun Mi’mah; Ahmad Asyrofi; Triana Arisdiani; Yulia Ardiyanti (Jurnal Surya Muda, 2023)
Hypertension is still a health problem that is quite high from all reported non-communicable diseases. Hypertension will cause complications such as heart disease, stroke, kidney failure if hypertensive patients have poor self-care. Complications can be prevented by doing good self care to improve the patient's quality of life. One of the interventions that can be used to improve self-care is peer group support. The measuring instrument uses a Self Care Management Behavior Questionnaire which is valid and reliable. The research design used Quasi Experimental with the Nonequivalent Control Group Design method pretest-posttest. The sample used was hypertensive clients who took prolanis at the Patebon 02 health center with a total of 30 respondents as a peer group support group and 30 respondents as a control group. The sampling technique used was total sampling. Statistical test using Wilcoxon and Chi Square. The results of the study obtained a p value of 0.0001 (p <0.05), which means that there is an influence of peer group support on self care of hypertensive clients.